The Role of Women in Gili Balu Ecotourism Development, West Sumbawa Regency - Putrawan Habibi; Muhammad Azizurrohman; Ander Sriwi; Supiandi Supiandi; Ihyana Hulfa (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: The purpose of this study is to identify the role played by women in the growth of ecotourism in Gili Balu, West Sumbawa Regency, as well as the barriers to that involvement. Method: This study was carried out in the villages of Poto Tano, Senayan, Tambak Sari, and Kiantar in the West Sumbawa Regency of the West Nusa Tenggara Province. The research used a descriptive qualitative methodology, and the primary data were gathered through observation, documentation, and interviews with 32 female respondents. Secondary data were gathered from journals and other research-related sources. Result: According to this study, women in the Gili Balu region played a negligible part in the creation and use of tourist sites. Women's roles are only limited to carrying out tasks like traditional dancers, lodging providers, chefs, souvenir makers, and advertising. The key challenges that the community, particularly women, must overcome are related to family, culture, religion, capital, knowledge, and inadequate government support. Contribution: This study can be used as a resource by a variety of parties interested in examining the role of women in the Gili Balu region to design community development strategies that are necessary.